The Process of Developing Student Worksheets (LKPD) Model RADEC (Read, Answer, Discuss, Explain, and Create) As an Active Learning Tool for State Elementary School 041/VII Pulau-Pandan - Yona Ayu Lesti; Nasyariah Siregar; Tika Sari (al-Afkar, Journal For Islamic Studies, 2026)
This research was motivated by the lack of learning media capable of supporting active learning in science subjects in elementary schools. To address this problem, a learning medium was developed in the form of a worksheet (LKPD) using the RADEC (Read, Answer, Discuss, Explain, Create) model. This study used the Research and Development (R&D) method with a 4D development model, which includes the define, design, develop, and disseminate stages. The objectives of this study were: (1) to understand the process of developing a RADEC-based worksheet, (2) to assess the media's feasibility based on expert validation, and (3) to determine the media's level of practicality in supporting students' active learning. The results showed that the developed worksheet was considered feasible and very feasible. The language validation score was 75 (feasible), the material validation score was 82 (very feasible), and the media validation score was 85 (very feasible). Furthermore, the practicality test results showed that this media was very practical to use, with scores of 95 from teachers and 93.386 from students. Qualitatively, observations also show an increase in students' active learning, such as active participation in reading, discussions, explanations, and creative work. Therefore, the RADEC model student worksheets (LKPD) can be an effective learning medium for increasing student engagement and understanding in science learning.